Why read Hannah Arendt now - Bernstein, Richard J. (Cambridge, UK ; Medford, MA : Polity Press, 2018)
Recently there has been an extraordinary international revival of interest in Hannah Arendt. She was extremely perceptive about the dark tendencies in contemporary life that continue to plague us. She developed a concept of politics and public freedom that serves as a critical standard for judging what is wrong with politics today. 0 Richard J. Bernstein argues that Arendt should be read today because her penetrating insights help us to think about both the darkness of our times and the sources of illumination. He explores her thinking about statelessness and refugees; the right to have rights; her critique of Zionism; the meaning of the banality of evil; the complex relations between truth, lying, power, and violence; the tradition of the revolutionary spirit; and the urgent need for each of us to assume responsibility for our political lives. 0 This short and very readable book will be of great interest to anyone who wants to understand the forces that are shaping our world today
Statelessness and refugees -- The right to have rights -- Loyal opposition : Arendt's critique of Zionism -- Racism and segregation -- The banality of evil -- Truth, politics and lying -- Plurality, politics, and public freedom -- The American Revolution and the revolutionary spirit -- Personal and political responsibility
Includes bibliographical references
Keywords: Arendt, Hannah, -- 1906-1975 -- Criticism and interpretation; Arendt, Hannah, -- 1906-1975 -- Political and social views